If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5h+14=9h-5
We move all terms to the left:
5h+14-(9h-5)=0
We get rid of parentheses
5h-9h+5+14=0
We add all the numbers together, and all the variables
-4h+19=0
We move all terms containing h to the left, all other terms to the right
-4h=-19
h=-19/-4
h=4+3/4
| 9x-7=-5x+91 | | n–2+–6.9=–11.16 | | -2|x+7|+3=19 | | k+1.993=2.94 | | 1=14x-1 | | -b=2-4(b+8) | | 5x-3=11x-(6x-4) | | 5x+2×2(x-1)=3x+4 | | 10x-10=3x+4+6x-10 | | -1+5n=7+3n | | t/–2+7=10 | | 7=12x+17 | | 10x-10=3x+46x-10 | | 3y=7+5(y-3) | | 10-7(-5x+1)=35x+3 | | 4t-5.07=10.93 | | X+x*0.125=15 | | X+x•0.125=15 | | -16-3x=2(4-3x) | | 1.5(16x–6)=2. | | 12y-16=60 | | 6y+8-3y+6=2y | | (2y+34)74=180 | | 1/2=(-4b+6) | | 5x-9=-3(20) | | p2+10p=0 | | 27-7y=3 | | 4c=3(2c-5)+7 | | -3y+(-2)=-17 | | 3(u-1)=7u+2-7(-2u-1) | | 3x6x=180 | | 7f+5=9(f-7) |